Perkembangan Grup Randai di Kuantan Singingi: Studi Sejarah Sosial Budaya (1999-2023) - Aygilia, Aprina; Naldi, Hendra (AHKAM, 2024)
This study discusses the Socio Cultural life of Randai in Kuantan 1999-2023, the development of Randai culture and its resilience until now or can be said to exist. This research aims to explain the development of the randai group in Kuantan Singingi in 1999-2023. The aim of this research is to explain the culture and art, especially Randai art in the Kuantan regi0n. This research explains the development of Randai group in Kuantan Singingi in 1999-2023. The purpose of this research is to explain culture and art, especially Randai art in the Kuantan region, which can be said to be valid, Kuantan Singingi is truly a Minangkabau region. This research explains the colorful cultural growth and development of Randai and the reasons why Randai survives in Kuantan Singingi and even exists. This research includes qualitative research, using historical research methods. Qualitative research is a research procedure that produces descriotive data. The steps in historical research go throught four stages, namely heuristics (data collection), source criticism, interpretation ( interpreting historical evidence), amd historiography ( writing history). The data collection techniques used were archival studies, literature studies and interviews.